A CRITICAL REVIEW OF THE EXTENT TO WHICH THE HIV/AIDS AND HUMAN RIGHTS INTERNATIONAL GUIDELINES HAVE BEEN IMPLEMENTED IN THE SOUTHERN AFRICAN DEVELOPMENT COMMUNITY* - Ann Strode; Brenda Grant (Obiter, 2022)
2006 was the tenth anniversary of the development of the International Guidelines on HIV/AIDS and Human Rights and to celebrate this occasion the AIDS and Rights Alliance of Southern Africa (ARASA) commissioned research into the extent to which these Guidelines have been used and implemented in the Southern African Development Community (SADC) region. This article examines the findings of this research on the three guidance points related to developing a legal and policy framework. It finds that although reforms are taking place within the SADC region and many are aimed at ensuring that responses to HIV are based on human rights, there is an uneven approach, with a number of countries failing to meet the basic requirements described in the Guidelines. There are also a number of regional human rights issues that need to be addressed as a matter of urgency. These include the continued testing and exclusion of HIV-positive recruits from the military, the criminalisation of same-sex relationships and the lack of legal protection for women.